Differentiation and identification of Aedes albopictus Skuse from several population in Indonesia based on genetic polymorphisms - Budi Mulyaningsih, Budi Mulyaningsih (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2004)
Background: Aedes albopictus play important role in the spread dengue virus, it is spread widely in Indonesia. Geographical condition of Indonesia which shows varying climatology, biogeography and environmental factors seem to be very possible to cause the difference in the genetic structure of Ae. albopictus.Objective: The aim of this study is to determine the genetic polymorphism of each Ae. albopictus population.Methods: Genomic DNA was extracted from individual mosquitoes from 4 geographic populations of Ae, albopictus and amplified in PCR reactions using single primers of arbitrary nucleotide sequence.Result: The DNA polymorphism level of Ae. albopictus population originated from Yogyakarta is 80.77%, followed by population originated from Padang is 57.14%, Banjar is 40.74% and Timika is 37.50%. Conclusion: The genetic structure of the Ae. albopictus populations shows obvious differences, and they shows that they are from different group and separated with the various difference percentage.Key words: genetic polymorphism - population - Ae. albopictus - dengue virus - RAPD-PCR.